Incidental diagnosis of pseudomyxoma peritonei by laparoscopy: a rare case from Syria. Issue 12 (7th December 2022) - Brimo Alsaman, Muhamad Zakaria; Anbar, Ahmad; Nawlo, Ahmad; Almooay, Adeeb; Darwish, Ahmad; Mohammad, Mazen
Abstract: Pseudomyxoma peritonei (PMP) is a rare malignancy of the abdomen, which is usually described as a gelatinous peritoneal fluid. A 33-year-old man came to the ER complaining of recurring abdominal pain with abdominal distention for the past 3 months. Abdominal ultrasound revealed moderate amount of turbulent ascitic fluid with septations, in addition to a mass with irregular margins consisting of liquid and cysts. Abdomen and pelvis computed tomography scan showed free abdominal fluid. A decision was made for abdominal diagnostic laparoscopy with biopsies from the peritoneum, mesenteries and the gelatinous fluid. We could not investigate all the abdominal cavities and appendix due to the presence of severe adhesions and tuberculosis suspension. The pathology report indicated PMP. The patient was referred to an oncologist for chemotherapy consultation. The diagnosis can be challenging, as the symptoms and signs vary from patient to another; most cases may be asymptomatic and discovered incidentally during laparoscopy.